The Influence of Mental Health and Job Insecurity on Job Performance with Psychological Resilience as A Moderator in Generation Z E-Commerce Employees - Ramadhan, Wahyu; Rachmawati, Riani (Jurnal Ilmiah Sumber Daya Manusia, 2024)
E-commerce workers are prone to experiencing stress, anxiety, job insecurity and depression due to high work pressure and mass layoffs. This study aims to analyze the moderating role of resilience to job insecurity and mental health on the performance of Gen Z employees in Indonesia. Questionnaires were given to 290 employees of the top 5 e-commerce companies in Indonesia using a purposive sampling technique, with an analytical technique using SEM-PLS. The measurement tools used are SRQ-20 (Self-Reporting Questionnaire -20), IPWQ (Individual Performance Work Questionnaire), JIS (Job Insecurity Scale). The results of the study show that good mental health conditions have a positive effect on employee performance with moderation of psychological resilience increasing the positive effect of mental health. Meanwhile, job insecurity has a negative effect on employee performance and employees with high psychological resilience will reduce the negative effect of job insecurity on employee performance.